The Effect of Bajakah Kalalawit (Uncaria gambir) Stem Extract on Spermatozoa Viability In Vitro - Silvani Permatasari; Fitha Nadia Artika; Septi Handayani; Ratna Widayati; Elsa Trinovita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The prevalence process impairs sperm biochemistry and function by generating high levels of Reactive Oxygen species (ROS) and damaging sperm cells. In addition, ROS imbalance leads to decreased sperm viability, mitochondrial dysfunction, and DNA damage. The administration of Bajakah Kalalawit stem extract (Uncaria gambir (W. Hunter) Roxb.) is stated to maintain sperm quality. In vitro sperm viability tests have not been widely conducted. This study aims to determine the effect of Bajakah Kalalawit stem extract (Uncaria gambir (W. Hunter) Roxb.) on sperm viability in vitro. This research is experimental research, the type of design used is posttest only with control group design. The sample was determined by consecutive sampling and the samples taken were 15. The statistical test using LSD Post-Hoc test obtained between groups there were significant differences with p <0.05. The compounds contained in the ethanol extract of Bajakah Kalalawit stem (Uncaria gambir (W. Hunter) Roxb.) are terpenoids, flavonoids, steroids, saponins and alkaloids. Viability of spermatozoa increased significantly from the concentration of 50ng/mL with a percentage of 74.13%, 100ng/mL by 83.00%, 500ng/mL by 87.60% and 1000ng/mL by 91.27%. The ethanol extract of Bajakah Kalalawit stem (Uncaria gambir (W. Hunter) Roxb.) can affect the viability of spermatozoa in vitro.